2010
DOI: 10.1007/s11270-010-0361-9
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Contamination in Rice, Wheat, Pulses, and Vegetables: A Study in an Arsenic Affected Area of West Bengal, India

Abstract: Ganga-Meghna-Bramhaputra basin is one of the major arsenic-contaminated hotspot in the world. To assess the level of severity of arsenic contamination, concentrations of arsenic in irrigation water, soil, rice, wheat, common vegetables, and pulses, intensively cultivated and consumed by the people of highly arsenic affected Nadia district, West Bengal, India, were investigated. Results revealed that the arsenic-contaminated irrigation water (0.318-0.643 mg l -1 ) and soil (5.70-9.71 mg kg -1 ) considerably inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(75 citation statements)
references
References 45 publications
(82 reference statements)
5
66
3
1
Order By: Relevance
“…Arsenic uptake achieved by sunflower in the present study indicates that the plant is not a suitable candidate for phyto-extraction purposes. Although the quantity of arsenic present in sunflower shoot is not comparable to that obtained in other studies by using hyper accumulating plants (Wei et al 2010), the results evidenced that the arsenic up taken by sunflower exceeded the limit reported for food crops (1 mg kg -1 ) (Bhattacharya et al 2010). This confirms the estimation made by Warren et al (2003) which states that crops grown in soil with more than 200 mg kg -1 arsenic cause food poisoning.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Arsenic uptake achieved by sunflower in the present study indicates that the plant is not a suitable candidate for phyto-extraction purposes. Although the quantity of arsenic present in sunflower shoot is not comparable to that obtained in other studies by using hyper accumulating plants (Wei et al 2010), the results evidenced that the arsenic up taken by sunflower exceeded the limit reported for food crops (1 mg kg -1 ) (Bhattacharya et al 2010). This confirms the estimation made by Warren et al (2003) which states that crops grown in soil with more than 200 mg kg -1 arsenic cause food poisoning.…”
Section: Discussioncontrasting
confidence: 74%
“…Although sunflower (Helianthus annuus L.) has been proposed for phyto-extraction purposes because it uptakes relatively high concentrations of metals and can have high biomass yield (Marchiol et al 2007), literature is scarce about its ability to translocate arsenic. Arsenic uptaken by food crops should not exceed the limit of 1 mg kg -1 (Bhattacharya et al 2010) and health hazards for food poisoning might be present when crops grow in soils with arsenic content higher than 200 mg kg -1 (Warren et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated that exposure to higher levels of As led to a decrease in biomass production for both shoot and root tissues of rice plants during the vegetative development stage, as was previously reported by others authors (Geng et al 2009, Bhattacharya et al 2010 (Figure 2). Overall, regardless the P level or As exposure, the cultivar IRGA 424 had higher values of root and shoot dry weight as well as total root length and number of root tips as compared to BR-IRGA 409; while IRGA 423 seems to be in an intermediate condition between the other two cultivars ( Figure 2, Figure 3).…”
Section: Resultssupporting
confidence: 90%
“…In vivo studies conducted in the study area revealed that different rice varieties have different potential in accumulating arsenic from the same arsenic-contaminated irrigation water and paddy field soil [8,9,10,11]. The induction of arsenic in human food chain through consumption of rice thus imposes community health risk in arsenic affected areas of West Bengal [12,13].…”
Section: Introductionmentioning
confidence: 99%